Textos originais de cientistas e textos sobre história das ideias da ciência em uma proposta didática sobre ótica na formação inicial de professores de física - Schirmer, Saul Benhur (2012)
Science Teaching in Brazil has been increasingly acknowledged as a research field and has also been seeking for alternatives to improve scientific education in all levels. One of the research fields is the incorporation of History and Philosophy of Science (HFC) in education, which has received significant attention by government guidelines and researchers in the field. This work presents the results obtained by the implementation of a HFC related didactic module with undergraduate students from UFSM s course of Physics. The purpose of this work was to evaluate the use of Scientists Original Texts (TOC) and History of Scientific Ideas Texts (THIC) in Science Teaching, more specifically in Physics Teaching. In order to subsidize the elaboration of the module, we performed a research in the field magazines and events, trying to ascertain to what extent these publications concern class works and which are the resources used. The results were classified in classroom approaches or HFC subsidies. The results show that there is a low number of classroom approaches, and the main resources for HFC use in the classroom are texts. The results also show that there are almost no reports of the use of TOC and THIC in undergraduate courses. Optics was the chosen theme and conceptual aspects, nature of science aspects and the aspects concerning the requirements of teacher formation were considered. The results, obtained by the application of questionnaires during the length of classes, have indicated an advancement concerning students conceptions about science. They also have indicated that few students succeeded in using the discussions about Optics conceptual contents in the questions proposed. According to the research analysis, there was great acceptance about the texts, especially the ones concerning THIC. Based on the results, we propose didactic module changes and other possible research developments.